1999
DOI: 10.1080/00224549909598248
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Racial Differences in Mathematical Performance

Abstract: The authors examined gender and racial differences in mathematics performance among 5th- and 8th-grade students in the United States. Math performance was assessed by scores on the math-concepts and math-computation sections of the California Achievement Test (CTB/McGraw-Hill, 1986) given at the end of the previous year. There were no significant gender differences, but in both grades, the White students scored significantly higher than the Black students. The racial differences were more pronounced in the sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
34
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(42 citation statements)
references
References 12 publications
5
34
0
3
Order By: Relevance
“…Buna göre, anne-babaların eğitim seviyesi yükseldikçe çocukların akademik başarılarının bariz bir şekilde yükseldiği görülmektedir. Bu ilişkiyi doğrulayan başka araştırmalarda bulunmaktadır (Akyol, Sungur ve Tekkaya, 2010;DeGarmo, Forgatch ve Martinez, 1999;Hall, Davis, Bolen ve Chia, 1999;Hortaçsu, 1994;Kuyper, Van der Werf ve Lubbers, 2000;Öksüzler ve Sürekçi, 2010;Yılmaz, 2000). Bu araştırmalardan bazılarında çocuğun akademik başarısında annenin (Hall vd., 1999;Hortaçsu, 1994;Öksüzler ve Sürekçi, 2010;Yılmaz, 2000), bazılarında ise babanın (Alomar, 2006;Anıl, 2009;Hortaçsu, 1995;Keskin ve Sezgin, 2009;Özer ve Anıl, 2011) daha etkili olduğu bulunmuştur.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…Buna göre, anne-babaların eğitim seviyesi yükseldikçe çocukların akademik başarılarının bariz bir şekilde yükseldiği görülmektedir. Bu ilişkiyi doğrulayan başka araştırmalarda bulunmaktadır (Akyol, Sungur ve Tekkaya, 2010;DeGarmo, Forgatch ve Martinez, 1999;Hall, Davis, Bolen ve Chia, 1999;Hortaçsu, 1994;Kuyper, Van der Werf ve Lubbers, 2000;Öksüzler ve Sürekçi, 2010;Yılmaz, 2000). Bu araştırmalardan bazılarında çocuğun akademik başarısında annenin (Hall vd., 1999;Hortaçsu, 1994;Öksüzler ve Sürekçi, 2010;Yılmaz, 2000), bazılarında ise babanın (Alomar, 2006;Anıl, 2009;Hortaçsu, 1995;Keskin ve Sezgin, 2009;Özer ve Anıl, 2011) daha etkili olduğu bulunmuştur.…”
Section: Tartışma Sonuç Ve öNerilerunclassified
“…Further, there is a significant negative correlation for affective (emotional) anxiety and performance in math courses (Ho et al, 2000). In addition, parents' attitudes about math are a factor in math anxiety and test performance (Hall et al, 1999). The net result is both math avoidance and poor performance in math courses.…”
Section: Math Anxiety: Interventions For Studentsmentioning
confidence: 99%
“…In particular, the role played by gender has been studied (Segal, 1987;Harrington et al, 1992;Hall et al, 1999;Ho et al, 2000). Studies of middle school students indicated that gender is a predictor of math anxiety.…”
Section: Math Anxiety: Interventions For Studentsmentioning
confidence: 99%
“…Fakat bu sayısal alanlara karşı gerek yetenek, gerekse başarı açısından cinsiyetler arasında anlamlı bir fark olmadığını öne süren çalışmalara son yıllarda, hem fen (Cole, 1997;Keeves, 1992;Martin ve diğ., 2008;Spelke, 2005), hem de matematik (Beller ve Gafni, 1996;Hall, Davis, Bolen ve Chia, 1999;Hyde, Fennema ve Lamon, 1990;Mullis ve diğ., 2008;Sakız, 2012) literatüründe daha sık rastlanmaktadır. Hatta, fen ve matematik başarısı açısından kızlar lehine farklar bulan çalışmaların (Bulut, Gür ve Sriraman, 2010;Bursal, 2013; Eğitimi Araştırma ve Geliştirme Dairesi [EARGED], 2007a;Koca, 2011;Martin, Mullis, Foy ve Stanco, 2012;Mullis, Martin, Foy ve Arora, 2012;Özay, Ocak ve Ocak, 2003;Yıldırım, Yıldırım, Yetişir ve Ceylan, 2013) sayısının gittikçe arttığı da gözlenmektedir.…”
unclassified